Purification, characterization and antioxidant activity of polysaccharides from Flammulina velutipes residue. (10th July 2016) - Liu, Ying; Zhang, Bin; Ibrahim, S.A.; Gao, Shuang-Shuang; Yang, Hong; Huang, Wen
Highlights: Three kinds of heteropolysaccharides were purified from F. velutipes residue. The structural characteristics of FVRP-1, FVRP-2 and FVRP-3 were different. FVRP-1, FVRP-2 and FVRP-3 had good scavenging ability on hydroxyl and ABTS + radicals. Abstract: In this study, we isolated polysaccharides from Flammulina velutipes residue (FVRP) using microwave-assisted extraction and then purified the polysaccharides by column chromatography to yield FVRP-1, FVRP-2 and FVRP-3. The structural characteristics of FVRP-1, FVRP-2 and FVRP-3 were investigated, and their antioxidant activities against ABTS +, DPPH and hydroxyl radicals were also analyzed in vitro . FVRP-1 was found to be neutral and rich in galactose. However, FVRP-2 and FVRP-3 were acidic polysaccharides and were rich in glucose. The average molecular weight of FVRP-1, FVRP-2 and FVRP-3 were 29, 930, 62, 290, and 36, 310 Da, respectively. The glycosyl residue of FVRP-1 was an α-type glycosidic linkage, whereas FVRP-2 and FVRP-3 were β-type glycosidic linkages. We found FVRP-1, FVRP-2 and FVRP-3 had strong potential antioxidant activities in the order of FVRP-1 < FVRP-3 < FVRP-2. Our results thus suggested that FVRPs might be suitable for use as functional foods and as potential therapeutic agents.